Bibliometric analysis of research on China’s rural environmental governance in CNKI and WOS - Shen, Qin; Sun, Qing; Zhao, Aopei (Frontiers in Environmental Science, 2024)
At present, the global consensus on the concept of sustainable development continues to deepen, and China’s ecological civilization construction and rural revitalization strategy continue to advance. However, the rural environmental situation in China is becoming more and more complex. Therefore, a comprehensive review and summary of China’s rural environmental governance research are particularly important, which can not only provide theoretical support for future research but also offer vital guidance for governance practices. Based on the research literature of CNKI (1993-2023) and WOS (2001-2024), bibliometrics and CiteSpace software are adopted in this review to tease out the main characteristics, research hotspots and evolution trends of rural environmental governance research in China. The results indicate that: (1) Research interest shows an overall upward trend, with an expanding scale of interdisciplinary scholars and teams emerging. The collaboration network among authors and institutions in WOS appears tighter than that in CNKI. (2) In CNKI, Research hotspots revolve around environmental issues and pollution governance, social participation and governance mechanisms, ecological civilization and sustainable development, and rural revitalization and construction. In WOS, research hotspots pivot towards policy implementation and governance mechanisms, environmental issues and resource management, socio-economic impacts and equity, information disclosure and community participation, and technology and methods. (3) The research in CNKI has undergone three stages: “initiation”, “development”, and “deepening”. In contrast, the research in WOS started relatively late and is currently still in the “development” stage. Future research should focus on enhancing disciplinary integration and fostering collaboration among domestic and international scholars and institutions. Under the rural revitalization strategy, focus should be on achieving symbiosis between rural economic growth and ecological civilization construction. Simultaneously exploring diverse stakeholder governance models, focusing on rural living environment issues and striving to reduce rural carbon emissions to address climate change challenges.